Damage at high strain rates in semi-crystalline polymers. (February 2015) - Balieu, R.; Lauro, F.; Bennani, B.; Haugou, G.; Chaari, F.; Matsumoto, T.; Mottola, E.
Abstract: A specific damage characterization method using Digital Image Correlation for semi-crystalline polymers is proposed for a wide range of strain rates. This damage measurement is an extension of the SEĖ method [16] which was developed to characterize the behaviour laws at constant strain rates of polymeric materials. This procedure is compared to the well-known damage characterization by loss of stiffness technique under quasi-static loading. In addition, an in-situ tensile test, carried out in a microtomograph, is used to observe the cavitation phenomenon in real time. The different ways used to evaluate the damage evolution are compared and the proposed technique is also suitable for measuring the ductile damage observed in semi-crystalline polymers under dynamic loading. Highlights: The proposed damage characterization technique is performed by Digital Image Correlation. The new damage characterization is compared with the classical loss of stiffness technique. The cavitation phenomenon is observed by in-situ tensile test with micro-tomographe. The damage evolution is measured in quasi-static and dynamic.